2011
DOI: 10.3390/md9071210
|View full text |Cite
|
Sign up to set email alerts
|

A New Hydroxylated Nonaprenylhydroquinone from the Mediterranean Marine Sponge Sarcotragus spinosulus

Abstract: Chemical investigation of the Mediterranean sponge Sarcotragus spinosulus led to the isolation of a new hydroxylated nonaprenylhydroquinone, along with two known metabolites, hepta- and octaprenylhydroquinones. The structure of the new metabolite was assigned by extensive 1D and 2D NMR analyses and MS studies. The antileukemic effect of the three compounds towards the chronic myelogenous leukemia (CML) cells line K562 was also evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
1
20
2
1
Order By: Relevance
“…S. spinosulus is amassive horny sponge with a regular conulose,black to grey surface, and white to light brown interior. This photophilousdemosponge is commonly found in shallow waters, mainly in the Western Mediterranean coasts (Abed et al, 2011;Mercurio et al, 2013;Murray et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. spinosulus is amassive horny sponge with a regular conulose,black to grey surface, and white to light brown interior. This photophilousdemosponge is commonly found in shallow waters, mainly in the Western Mediterranean coasts (Abed et al, 2011;Mercurio et al, 2013;Murray et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…spinosulus(named Irciniaspinosula in previous works) is a natural producer of linear polyprenylhydroquinones (Cimino et al, 1972). This group of aromatic organic compounds exhibit moderate antibacterial, antiviral, anti-inflammatory and cytotoxic activities (Abed et al, 2011). Moreover, it comprises precursors of a new class of drugs regulating glutamatergic and cholinergic transmission in the mammalian central nervous system (Bisio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this species has also been found to contain terpenes with cytotoxic effects against cancer cells (Liu et al, 2001) and possible antitumor activities, which is a finding that should be confirmed through further study (Abed et al, 2011). In addition, other sponge-derived terpenoids could possess anti-inflammatory properties.…”
Section: Secondary Metabolites Of Sponges With Diverse Bioactivitiesmentioning
confidence: 61%
“…All isolated compounds were identified by comparison of their spectral data (see Supplementary Material, available online at http://dx.doi.org/10.1155/2016/5318176) with the literature values [16, 26, 3944]. …”
Section: Methodsmentioning
confidence: 99%